Structure optimization of ladle rotary table mounting device - Z. Cui; H. Y. Long; R. Q. Gong; F. Y. Zhu; W. Z. Yan (Metalurgija, 2024)
As a widely used equipment in continuous casting process, the installation process of ladle rotary table is complicated and requires many installation equipment. According to the practical engineering application, this paper takes the installation device as the research object, and optimizes the original structure of the installation device. SolidWorks software was used to model the overall structure of the installation device, and the established model was imported into Hypermesh for mesh division, and finally into ANSYS for finite element analysis to compare the stress and deformation of the structure before and after optimization.The results show that the stress of the optimized structure is reduced to some extent, and the practical application requirements are met.